Development of the sepak takraw basic skills test for junior athletes - Hidayat, Rohman; Febriani, Ayu Rizki; Budi, Didik Rilastyo; Kusuma, Indra Jati; Khurrohman, Moch Fath (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Problems: Basic skills are needed in the sport of sepak takraw, so in this case an instrument is needed that can be used as a valid measurement tool to support the coaching and training process for junior athletes aged 12-15 years. Purpose: This study aims to develop a basic sepak takraw skills test for athletes aged 12-15 years based on the validity of the content and empirical validity carried out. Methods: The research method used is Research and Development (RnD) through 7 stages of research. The research subjects used amounted to 20 samples for small scale, and 40 samples for large scale. The data analysis technique used uses quantitative descriptive analysis. Results: The expert validity test provides recommendations that the instruments that developed already worth using. Based on the results of the validity and reliability test, it shows a content validity value of 0.89 and a feasibility value of 90.3%. Conclusion: The results show that the developed instruments have qualified as measuring instruments and are feasible to apply to measure the basic sepak takraw skills of junior athletes. Keywords: Development, test instruments, sepak takraw.